Sub-assembly for all-solid-state battery, all-solid-state battery, and method for preparing all-solid-state battery
By using sub-assembly of the porous carbon material intermediate layer in an all-solid-state battery, the problems of poor contact between the negative electrode current collector and the solid electrolyte layer and weakened mechanical structure are solved, and the charging and discharging characteristics are improved and the battery performance is improved.
Patent Information
- Application Number
- CN202411300815.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-13
- Filing Date
- 2024-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing all-solid state batteries have poor contact and weakened mechanical structure between the negative electrode current collector and the solid electrolyte layer, resulting in deterioration of charging and discharging characteristics.
A subassembly comprising an intermediate layer of porous carbon material consisting of a first intermediate layer with partially or completely lithium-filled pores, a second intermediate layer without lithium-containing pores and a third intermediate layer containing metals is enhanced to enhance the mechanical structure and electrochemical contact between the negative electrode current collector and the solid electrolyte layer.
Improve the charging and discharging characteristics, enhance the mechanical structure of the battery, and improve the performance of the unit battery.
Smart Images

Figure CN119650590A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0124085 filed on September 18, 2023, and Korean Patent Application No. 10-2024-0125245 filed on September 13, 2024, in the Korean Intellectual Property Office, the contents of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present disclosure relates to subassemblies used in all-solid-state batteries, all-solid-state batteries, and methods of making the same. Background Art
[0004] In order to develop batteries with higher energy density and safety, all-solid-state batteries using solid electrolytes instead of flammable organic electrolytes have been proposed. All-solid-state batteries use a negative electrode active material layer of lithium or lithium alloy, or a negative electrode current collector on which a negative electrode active material layer is not formed during manufacturing as a negative electrode.
[0005] There still exists a need for an all-solid-state battery having a structure that can enhance contact between a negative electrode current collector and a solid electrolyte layer while strengthening the mechanical structure therebetween, thereby improving charge and discharge characteristics, and a method of preparing the same. Summary of the invention
[0006] A subassembly for use in an all-solid-state battery having a reinforced mechanical structure and improved charge / discharge characteristics is provided.
[0007] An all-solid-state battery including the subassembly is provided.
[0008] A method for preparing the all-solid-state battery is provided.
[0009] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0010] According to one aspect of the present disclosure, a subcomponent for use in an all-solid-state battery is provided, comprising a negative electrode current collector, an intermediate layer, and a solid electrolyte layer, wherein in its initial state or fully discharged state, the intermediate layer comprises: a first intermediate layer containing a porous carbon material, which contacts the solid electrolyte layer and comprises a porous carbon material having pores partially or completely filled with lithium; a second intermediate layer containing a porous carbon material, which comprises pores that do not contain lithium and is disposed on the first intermediate layer containing the porous carbon material; and a third intermediate layer containing a metal, which contacts the negative electrode current collector and is on the second intermediate layer containing the porous carbon material, wherein the third intermediate layer containing a metal comprises a metal.
[0011] According to another aspect of the present disclosure, an all-solid-state battery includes a positive electrode and the subassembly on the positive electrode, the positive electrode including a positive electrode current collector and a positive electrode active material layer.
[0012] According to another aspect of the present disclosure, a method for preparing an all-solid-state battery includes: preparing a solid electrolyte molded body (molded body), surface treating the solid electrolyte molded body to provide a treated surface, applying an intermediate layer containing a porous carbon material on one side of the solid electrolyte layer, drying the intermediate layer containing the porous carbon material to prepare the solid electrolyte layer having the intermediate layer containing the porous carbon material on one side, and disposing the negative electrode collector on the intermediate layer containing the porous carbon material; attaching a first metal foil provided with a first metal lithium to a surface of the solid electrolyte layer opposite to a surface on which the intermediate layer containing the porous carbon material is provided, so as to obtain a layer including the negative electrode collector / the intermediate layer containing the porous carbon material / the solid electrolyte. layer / the first metallic lithium / the first metallic foil, pre-lithiating the first metallic foil under vacuum to obtain a second metallic foil comprising the negative electrode current collector / a second intermediate layer containing a porous carbon material having pores not containing lithium / a first intermediate layer containing a porous carbon material having pores partially or completely filled with lithium / the solid electrolyte layer / the first metallic lithium / the first metallic foil, removing the first metallic foil on which the first metallic lithium is disposed from the second stack and disposing the second metallic foil between the second intermediate layer containing the porous carbon material and the negative electrode current collector to form a third intermediate layer containing metal, thereby preparing the subassembly described above; and disposing a positive electrode on the solid electrolyte layer of the subassembly to prepare the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The above and other aspects, features and advantages of some embodiments of the present disclosure will become more apparent from the following description considered in conjunction with the accompanying drawings, in which:
[0014] Figure 1A cross-sectional view showing an embodiment of a subassembly for use in an all-solid-state battery;
[0015] Figure 2 A schematic diagram is shown for explaining the effect of a sub-assembly used in an all-solid-state battery;
[0016] Figure 3A A schematic process flow diagram showing an embodiment of a method for preparing a negative electrode portion including a solid electrolyte layer and an intermediate layer;
[0017] Figure 3B A schematic process flow diagram showing an embodiment of a method for preparing an all-solid-state battery;
[0018] Figure 4 Shows the results of scanning electron microscope (SEM) analysis by disassembling the subassembly of the negative electrode-solid electrolyte layer of the all-solid-state secondary battery prepared according to Example 1;
[0019] Figures 5A to 5D The results of Auger electron spectroscopy (AES) analysis of the subassembly of the negative electrode-solid electrolyte layer of the all-solid-state secondary battery prepared according to Example 1 are shown;
[0020] Figure 6 An image of an X-ray photoelectron spectroscopy (XPS) analysis sample labeled P1 (center portion) to P5 (edge portion) on the surface of an intermediate layer containing a porous carbon material on a solid electrolyte layer is shown after removing a bag and a negative electrode from a pre-lithiated second stack of an all-solid secondary battery prepared according to Example 1;
[0021] Figures 7A to 7E Display for Figure 6 XPS analysis results of lithium, carbon, oxygen, and chlorine distributed in the middle layer containing porous carbon material in samples 1 (P1) (central part), 2 (P2), 3 (P3), 4 (P4), and 5 (P5) (edge part).
[0022] Figures 8A to 8E Shows the results of a total of 26 cycles of charge and discharge experiments in a constant temperature bath at 25°C for all-solid-state secondary batteries prepared according to Example 1, Example 2, and Comparative Examples 1 to 3; and
[0023] Fig. 9A and 9B The results of charging and discharging experiments for a total of 30 cycles in a constant temperature bath at 25° C. for all-solid-state secondary batteries prepared according to Example 1, Example 2, and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0024] Embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following only describes the embodiments to illustrate aspects by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. Expressions such as "at least one (kind)" when before or after a list of elements modify the entire list of elements and do not modify the individual elements of the list.
[0025] The inventive concept described below may be subjected to various transformations and may have various embodiments. Therefore, specific embodiments are shown in the accompanying drawings and described in detail in the detailed description. However, this is not intended to limit the inventive concept to specific embodiments, and should be understood to include all transformations, equivalents, or substitutes included in the technical scope of the inventive concept.
[0026] The terms used below are only used to describe specific embodiments and are not intended to limit the inventive concept. A singular expression includes a plural expression unless the context clearly dictates otherwise.
[0027] In this specification, the expression "at least one type", "one or more types", or "one (individual) or more (individual)" in front of the component (component) may supplement the entire component list, and may not supplement the individual component (component) described. The term "combination" used in this article includes mixing, alloys, reaction products, etc., unless otherwise specifically stated. The term "comprising" used in this article refers to further including other components (components), rather than excluding other components (components), unless otherwise specifically stated. The terms "first" and "second" do not represent order, amount, or importance, but are used to distinguish one element from another. Unless otherwise specified in this article or clearly contradictory to the context, it should be interpreted as including both the singular and the plural. "Or" refers to "and / or", unless otherwise specified.
[0028] Throughout this specification, "(an) embodiment," "an embodiment," etc. refer to situations in which a particular element described with respect to an embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. In addition, it should be understood that the described elements may be combined in any suitable manner in the various embodiments.
[0029] Unless otherwise stated, all percentages, parts, ratios, etc. are based on weight. In addition, when amounts, concentrations, or other values or parameters are given as ranges, preferred ranges, or lists of upper and lower preferred values, it should be understood that all ranges are formed by any upper range limit or upper preferred value and any lower range limit or lower preferred value, or any pair of preferred values, regardless of whether ranges are disclosed individually.
[0030] When a range of values is stated herein, unless otherwise stated, the range is intended to include the endpoints and all integers and fractions within the range. It is not intended that the scope of the present disclosure be limited to the specific values recited when defining a range.
[0031] Unless otherwise specifically stated, the unit "parts by weight" refers to a weight ratio between corresponding components, and the unit "parts by mass" refers to a value obtained by converting the weight ratio of the corresponding components into a solid content.
[0032] The term "about" as used herein includes the stated value and refers to within an acceptable range of deviation relative to a particular value as determined by one skilled in the art taking into account measurement-related errors and the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, 20%, 10%, or 5% relative to a specified value.
[0033] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this specification have the same meanings as those commonly understood by those skilled in the art to which the present disclosure belongs. It will also be understood that terms, such as those commonly used and defined in dictionaries, should be interpreted as having meanings consistent with their meanings in the context of the relevant art and the present disclosure, and should not be interpreted as idealized. In addition, they should not be interpreted in an overly formal sense.
[0034] Example embodiments are described herein with reference to cross-sectional views that are schematic diagrams of idealized embodiments. Therefore, the shape of the embodiment may change, for example, due to manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be interpreted as being limited to the specific shapes of the regions as described herein, but should include deviations in shape that occur, for example, during manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated acute angles may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shape of the regions or to limit the scope of the claims.
[0035] All-solid-state batteries have been prepared using cold isostatic pressing (CIP) and / or warm isostatic pressing (WIP). However, in all-solid-state batteries prepared by these methods, and although not wanting to be bound by theory, it is understood that due to high pressure and low or high temperature, after assembly, a gap region or void may be left between the negative electrode current collector and the solid electrolyte layer. As a result, the interface resistance between the negative electrode and the solid electrolyte layer of the all-solid-state battery increases, and the charge and discharge characteristics deteriorate.
[0036] In addition, during charging and discharging, and although not wanting to be bound by theory, it is understood that when an all-solid-state battery having a "Li-free" (or anode-free) structure is repeatedly subjected to the process of lithium dissolution and lithium deposition, voids are formed between the anode and the solid electrolyte layer, and the interface resistance therebetween may increase.
[0037] In addition, when an all-solid-state battery of the structure is prepared by a pressing step and a heat treatment step using cold isostatic pressing (CIP) and / or warm isostatic pressing (WIP), good contact may not be maintained at the interface region between the negative electrode and the solid electrolyte layer, and thus a gap region or void may exist between the negative electrode and the solid electrolyte layer. Therefore, the charging and discharging characteristics of the all-solid-state battery are deteriorated.
[0038] Recently, in order to solve this problem, a method of applying a silver-carbon composite negative electrode has been used to improve the discharge capacity at low temperature and provide high energy density and long life characteristics. However, this method is applicable only when the solid electrolyte layer is a sulfide solid electrolyte, and the lithium disposed on the copper foil can only be attached using the cold isostatic pressing (CIP) method described above, which leads to the above-described problems.
[0039] The inventors of the present disclosure have proposed an all-solid-state battery having a new structure and a method for preparing the same, which can be applied to a wider range of solid electrolyte layers other than sulfide solid electrolytes, such as oxide solid electrolytes and polymer solid electrolytes, and solve these problems.
[0040] Hereinafter, a subassembly used in an all-solid-state battery, an all-solid-state battery, and a method of manufacturing the all-solid-state battery according to example embodiments will be described in more detail.
[0041] Figure 1 A cross-sectional view of an embodiment of a subassembly 10 for use in an all-solid-state battery is shown.
[0042] Figure 1 The subassembly 10 used in the all-solid-state battery has a "Li-free" (or negative electrode-free) structure in an initial state or a fully discharged state, in which the solid electrolyte layer 1, the intermediate layer 5, and the negative electrode current collector 6 are arranged in the stated order.
[0043] The intermediate layer 5 includes: a first intermediate layer 2 containing a porous carbon material, which includes a porous carbon material having pores partially or completely filled with lithium; a second intermediate layer 3 containing a porous carbon material, which includes a porous carbon material and has pores that do not contain lithium; and a third intermediate layer 4 containing a metal, which includes a layer containing a metal. The first intermediate layer 2 containing a porous carbon material is a layer having pores partially or completely filled with lithium and in contact with the solid electrolyte layer 1. The second intermediate layer 3 containing a porous carbon material has pores that do not contain lithium and is located on the first intermediate layer 2 containing a porous carbon material. The third intermediate layer 4 containing a metal is a layer containing a metal on the second intermediate layer 3 containing a porous carbon material and in contact with the negative electrode current collector 6.
[0044] Although I don't want to be bound by theory, Figure 2 A schematic diagram for explaining an effect for understanding the functioning of a subassembly used in an all-solid-state battery according to an embodiment is shown.
[0045] Figure 2 The subassembly 10 used in the all-solid-state battery has the following structure: its constituent layers are Figure 1 The same order is arranged in the cross-sectional view.
[0046] Regarding the intermediate layer 5, the first intermediate layer 2 containing porous carbon material may have fine-sized, nano-sized or micron-sized pores. Here, fine-sized pores refer to pores of 2 nm or less. Among these, large-sized pores and medium-sized pores play an important role in lithium transmission. Here, large-sized pores refer to pores of 50 nm or more. Medium-sized pores refer to pores of 2 nm to 50 nm. For example, the first intermediate layer 2 containing porous carbon material may have pores with a size of about 10 nanometers (nm) to about 50 nm, about 50 nm to about 100 nm, about 100 nm to about 200 nm, about 200 nm to about 500 nm, or about 500 nm to about 1000 nm. The first intermediate layer 2 containing porous carbon material may have a porosity of 30% or more. For example, the first intermediate layer 2 containing porous carbon material may have a porosity of 30% to 60%. In addition, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, or at least 99% of the pores of the first intermediate layer 2 containing the porous carbon material can be filled with lithium. For example, 100% of the pores of the first intermediate layer 2 containing the porous carbon material can be filled with lithium.
[0047] The first intermediate layer 2 and the second intermediate layer 3 may each include a one-dimensional porous carbon material and a three-dimensional porous carbon material.
[0048] The one-dimensional porous carbon material may include carbon nanotubes, carbon nanofibers, carbon nanowires, carbon nanorods, carbon nanobelts, or combinations thereof. For example, the one-dimensional porous carbon material may include carbon nanotubes, carbon nanofibers, carbon nanowires, carbon nanorods, or combinations thereof. The three-dimensional porous carbon material may include carbon black particles, graphite particles, carbon nanoflowers, carbon nanoprisms, carbon nanodiamonds, or combinations thereof. For example, the three-dimensional porous carbon material may include carbon black particles, graphite particles, or combinations thereof.
[0049] The one-dimensional porous carbon material and the three-dimensional porous carbon material can form a microporous carbon material channel inside the intermediate layer 5. The one-dimensional porous carbon material can provide a conductive path from the negative electrode to the solid electrolyte layer 1. The one-dimensional porous carbon material can provide a short conductive path for electrons from the negative electrode to the solid electrolyte layer 1. The three-dimensional porous carbon material can provide a lithium transport path from the solid electrolyte layer 1 to the negative electrode. The first intermediate layer 2 containing the porous carbon material has pores partially or completely filled with lithium, and can quickly supply lithium from the solid electrolyte layer 1 to the negative electrode by diffusion, and can also remove lithium. As a result, the subassembly 10 used in the all-solid-state battery can have an improved discharge capacity. In addition, even if the binder is used in a small amount, the subassembly 10 used in the all-solid-state battery can improve the unit cell performance by strengthening the mechanical structure between the solid electrolyte layer 1 and the negative electrode current collector 6.
[0050] Based on the total weight of the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material, the content of the one-dimensional porous carbon material may be about 0.01 weight percent (wt %) to about 1 wt %, about 0.02 wt % to about 1 wt %, about 0.04 wt % to about 1 wt %, about 0.08 wt % to about 1 wt %, or about 0.1 wt % to about 1 wt %.
[0051] The first intermediate layer 2 containing a porous carbon material and the second intermediate layer 3 containing a porous carbon material may each further include a two-dimensional porous carbon material. Even if the binder is used in a small amount, the two-dimensional porous carbon material can further improve the unit cell performance by strengthening the mechanical structure between the solid electrolyte layer 1 and the negative electrode current collector 6.
[0052] The two-dimensional porous carbon material may include graphene, carbon nanosheets, carbon plates, carbon flakes, MXene, or a combination thereof. MXene can be prepared by selective etching of element A in the MAX phase, which is a layered solid that is metallically conductive and connected by strong metallic bonds, ionic bonds, and covalent bonds. Examples of MXene include Ti 2 AlC、Ti 3 AlC 2 , or4 AlC 3 .
[0053] The first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material may each further include a metal material, the metal material including metal nanoparticles, metal nanowires, metal nanotubes, metal nanofibers, metal nanosheets, metal nanorods, alloys thereof, or combinations thereof. Examples of metal materials that may be included in the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material may include gold, platinum, palladium, silver, aluminum, bismuth, tin, zinc, or combinations thereof. Since the metal material is further included in the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material, the charging and discharging characteristics of the all-solid-state battery may be further improved.
[0054] For example, the metal material may be in the form of particles. The median particle diameter (D50) of the metal material may be about 4 micrometers (µm) or less, about 3 µm or less, about 2 µm or less, about 1 µm or less, or 0.5 µm or less. The lower limit of D50 is not particularly limited, and may be about 10 nm or more. D50 refers to the particle diameter value corresponding to 50% from the smallest particle when the total number of particles is 100% in the distribution curve accumulated in the order from the smallest particle diameter to the largest particle diameter. D50 can be measured by methods well known to those skilled in the art, such as by using a particle size analyzer, or by measuring from a transmission electron microscope (TEM) image or a scanning electron microscope (SEM) image. Another method for obtaining D50 is as follows: a measurement device using dynamic light scattering can be used for measurement, data analysis is performed to count the number of particles in each particle diameter range, and then D50 is obtained by calculation thereof. The mixing weight ratio of the metal material and the carbon material in each of the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material may be, for example, 10:1 to 1:10, 5:1 to 1:5, 4:1 to 1:4, 3:1 to 1:3, or 2:1 to 1:2, but is not necessarily limited to these ranges and may be selected depending on the desired characteristics of the all-solid-state battery.
[0055] The first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material may each further include a binder. The binder may be an aqueous (water-containing) binder, an organic binder, or a combination thereof. Examples of binders include: one or more types of polymers selected from the following: polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol grafted polyacrylic acid, polyvinyl alcohol grafted polymethacrylic acid, carboxymethyl cellulose, butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, styrene-butadiene rubber, styrene-butadiene-styrene rubber, acrylate-butadiene rubber, acrylonitrile-butadiene-styrene rubber, polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, polyisobutylene, polyethylene, polypropylene, and polyimide; or copolymers thereof.
[0056] For example, the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material may each include a water-soluble binder.
[0057] In the case where the solid electrolyte layer 1 is an oxide solid electrolyte, the use of the water-soluble binder can improve the bonding force with the solid electrolyte layer 1 while the reactivity of the water-soluble binder is kept at a low level. In addition, the use of the water-soluble binder can contribute to the reduction of the binder content due to the excellent bonding force with the solid electrolyte layer 1, and is environmentally friendly due to the use of water as a solvent.
[0058] Examples of water-soluble binders include: one or more types of polymers selected from the following: polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol grafted polyacrylic acid, and polymethacrylic acid grafted with polyvinyl alcohol; or copolymers thereof. Among these, one or more types of polymers selected from polyvinyl alcohol grafted polyacrylic acid and polyvinyl alcohol grafted polymethacrylic acid, or copolymers thereof can be used as the aqueous binder. Compared with linear polymers or copolymers, these grafted polymer or copolymer binders may not only have improved bonding force, but also have superior elasticity. Therefore, an all-solid-state battery including a grafted polymer or copolymer as a binder in the first intermediate layer 2 containing a porous carbon material and the second intermediate layer 3 containing a porous carbon material may have improved charging and discharging characteristics, such as coulombic efficiency and cycle characteristics.
[0059] The content of the binder may be about 0.1 wt % to about 7 wt % based on the total weight of the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material. Even when such a small amount of the binder is used, the bonding force between the solid electrolyte layer 1 and the negative electrode collector 6 is improved, and a strong mechanical structure can be obtained, thereby improving the unit cell performance.
[0060] If desired, the first intermediate layer 2 containing a porous carbon material and the second intermediate layer 3 containing a porous carbon material may further include a conductive polymer.
[0061] Examples of the conductive polymer are poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene (PAC), poly(p-phenylenevinylene) (PPV), polypyrrole (PPY), polycarbazole, polyindole, polyaza , polyaniline (PANI), polythiophene (PT), poly(3,4-ethylenedioxythiophene) (PEDOT), or poly(p-phenylene sulfide) (PPS). By further including a conductive polymer in the first intermediate layer 2 containing a porous carbon material and the second intermediate layer 3 containing a porous carbon material, the charging and discharging characteristics of the all-solid-state battery, such as coulombic efficiency and cycle characteristics, can be further improved.
[0062] The thickness ratio of the second intermediate layer containing the porous carbon material to the thickness of the first intermediate layer containing the porous carbon material may be 1:0.5 to 1:5, 1:1 to 1:5, 1:1.5 to 1:5, or 1:2 to 1:5. The intermediate layer 5 having this thickness range can increase the electronic contact area with the solid electrolyte layer to improve the unit cell performance.
[0063] For example, the thickness of the first intermediate layer 2 containing the porous carbon material may be about 1 μm to about 5 μm. For example, the thickness of the second intermediate layer 3 containing the porous carbon material may be about 5 μm to about 10 μm. The first intermediate layer 2 containing the porous carbon material may be a pre-lithiation layer.
[0064] An all-solid-state battery including a first intermediate layer 2 containing a porous carbon material having such a film thickness may have strong mechanical structural characteristics, and may have improved unit cell performance such as charge / discharge efficiency, discharge capacity, and capacity retention. In contrast, in the case of an all-solid-state battery prepared using cold isostatic pressing (CIP) and / or warm isostatic pressing (WIP), since the manufacturing process includes pressing and heat treatment steps, the thickness of the first intermediate layer 2 containing a porous carbon material may be increased to prevent the formation of a void between the negative electrode and the solid electrolyte layer 1. When the first intermediate layer 2 containing a porous carbon material is formed to have such a film thickness using cold isostatic pressing (CIP) and / or warm isostatic pressing (WIP), the charge and discharge characteristics of the all-solid-state battery are greatly reduced.
[0065] The second intermediate layer 3 containing the porous carbon material may change in thickness during charge and discharge, and lithium may be captured in at least some of the pores thereof.
[0066] The metal-containing third intermediate layer 4 may include lithium, indium, gallium, alloys thereof, or combinations thereof.
[0067] After charging, the all-solid-state battery may include one or more of the following in the first intermediate layer 2 containing the porous carbon material and the second intermediate layer 3 containing the porous carbon material: a metal, a carbon material, an alloy thereof with lithium, or a composite thereof. Examples of these alloys with lithium or composites thereof are: an alloy of lithium with one or more of gold, platinum, palladium, silver, aluminum, bismuth, tin, or zinc; or LiC 6 .
[0068] The negative electrode current collector 6 may include a material that does not react with lithium (i.e., does not form any alloy and any compound). Examples of the negative electrode current collector 6 are copper (Cu), aluminum (Al), nickel (Ni), titanium (Ti), cobalt (Co), or stainless steel. The negative electrode current collector 6 may include an alloy or a coating material of one or two or more of the metals described above. The negative electrode current collector 6 may be plate-shaped or foil-shaped.
[0069] The surface of the solid electrolyte layer 1 in contact with the first intermediate layer 2 containing porous carbon material may be uneven. The uneven surface of the solid electrolyte layer 1 can be obtained by surface treatment. Examples of surface treatment are chemical treatment, electropolishing, wet polishing, argon plasma etching, oxygen plasma cleaning, annealing, or exposure to high vacuum. The first intermediate layer 2 containing porous carbon material can penetrate the uneven surface of the solid electrolyte layer 1 and provide an increased contact area with the solid electrolyte layer 1, and form a stronger interlayer bond (bonding).
[0070] The solid electrolyte layer 1 may include an oxide solid electrolyte, a sulfide solid electrolyte, a polymer solid electrolyte, or a combination thereof.
[0071] Examples of oxide solid electrolytes may include one or more of the following: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2,0≤y<3),BaTiO 3 , Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT)(0≤x<1, 0≤y<1), Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -PbTiO 3 (PMN-PT), HfO 2 , SrTiO 3 , SnO 2 , CeO2 , Na 2 O, MgO, NiO, CaO, BaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , TiO 2 , SiO 2 , Li 3 PO 4 , Li x Ti y (PO 4 ) 3 (0 <x<2,0<y<3),Li x Al y Tiz(PO 4 ) 3 (0 <x<2,0<y<1,0<z<3),Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (0≤x≤1,0≤y≤1), Li x La y TiO 3 (0 <x<2,0<y<3),Li 2 O, LiOH, Li 2 CO 3 , LiAlO 2 , Li 2 O-Al 2 O 3 -SiO 2 -P 2 O 5 -TiO 2 -GeO 2 , or Li 3+x La 3 M 2 O 12 (M=Te, Nb, or Zr, wherein x is an integer of 1-10).
[0072] The oxide solid electrolyte can be prepared by a sintering method or by a casting method.
[0073] For example, the oxide solid electrolyte may be a garnet-based solid electrolyte.
[0074] For example, the garnet-based solid electrolyte may include an oxide represented by Formula 1
[0075] Formula 1
[0076] (Li x M1 y )(M2) 3-δ (M3) 2-ω O 12-z X z
[0077] Wherein x, y, z, δ, ω and z in Formula 1 satisfy the following conditions: 6≤x≤8, 0≤y<2, -0.2≤δ≤0.2, -0.2≤ω≤0.2, and 0≤z≤2,
[0078] M1 can be a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0079] M2 can be a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0080] M3 can be a monovalent cation, a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof, and
[0081] X can be a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof.
[0082] Examples of monovalent cations in Formula 1 are Na, K, Rb, Cs, H, and Fr, and examples of divalent cations in Formula 1 are Mg, Ca, Ba, and Sr. Examples of trivalent cations in Formula 1 are In, Sc, Cr, Au, B, Al, and Ga, and examples of tetravalent cations in Formula 1 are Sn, Ti, Mn, Ir, Ru, Pd, Mo, Hf, Ge, V, and Si. Examples of pentavalent cations in Formula 1 are Nb, Ta, Sb, V, and P.
[0083] M1 may be, for example, hydrogen (H), iron (Fe), gallium (Ga), aluminum (Al), boron (B), beryllium (Be), or a combination thereof. M2 may be lanthanum (La), barium (Ba), calcium (Ca), strontium (Sr), yttrium (Y), bismuth (Bi), praseodymium (Pr), neodymium (Nd), actinium (Ac), samarium (Sm), gadolinium (Gd), or a combination thereof, and M3 may be zirconium (Zr), hafnium (Hf), tin (Sn), niobium (Nb), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), tungsten (W), tantalum (Ta), magnesium (Mg), technetium (Tc), ruthenium (Ru), palladium (Pd), iridium (Ir), scandium (Sc), cadmium (Cd), indium (In), antimony (Sb), tellurium (Te), thallium (Tl), platinum (Pt), silicon (Si), aluminum (Al), or a combination thereof.
[0084] Regarding Formula 1, the monovalent anion used as X can be a halogen atom, a pseudohalogen, or a combination thereof, and the divalent anion can be S 2- or Se 2- , and the trivalent anion can be, for example, N 3- .
[0085] In Formula 1, x can be 6.6 ≤ x ≤ 8, 6.7 ≤ x ≤ 7.5, or 6.8 ≤ x ≤ 7.1.
[0086] For example, the garnet-based solid electrolyte can include an oxide represented by Formula 2
[0087] Formula 2
[0088] (Li x M1 y )(La a1 M2 a2 ) 3-δ (Zr b1 M3 b2 ) 2-ω O 12-z X z
[0089] Regarding Formula 2,
[0090] M1 can be hydrogen (H), iron (Fe), gallium (Ga), aluminum (Al), boron (B), beryllium (Be), or a combination thereof,
[0091] M2 can be barium (Ba), calcium (Ca), strontium (Sr), yttrium (Y), bismuth (Bi), praseodymium (Pr), neodymium (Nd), actinium (Ac), samarium (Sm), gadolinium (Gd), or a combination thereof, and
[0092] M3 can be hafnium (Hf), tin (Sn), niobium (Nb), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), tungsten (W), tantalum (Ta), magnesium (Mg), technetium (Tc), ruthenium (Ru), palladium (Pd), iridium (Ir), scandium (Sc), cadmium (Cd), indium (In), antimony (Sb), tellurium (Te), thallium (Tl), platinum (Pt), silicon (Si), aluminum (Al), or a combination thereof,
[0093] 6 ≤ x ≤ 8, 0 ≤ y < 2, -0.2 ≤ δ ≤ 0.2, -0.2 ≤ ω ≤ 0.2, 0 ≤ z ≤ 2,
[0094] a1 + a2 = 1, 0 < a1 ≤ 1, 0 ≤ a2 < 1,
[0095] b1 + b2 = 1, 0 < b1 ≤ 1, 0 ≤ b2 < 1, and
[0096] X can be a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof.
[0097] Regarding Formula 2, the monovalent anion used as X may be a halogen atom, a pseudohalogen, or a combination thereof, and the divalent anion may be S 2- or Se 2- , and the trivalent anion may be, for example, N 3- .
[0098] Regarding Formula 2, x may be 6.6≤x≤8, 6.7≤x≤7.5, or 6.8≤x≤7.1.
[0099] The term "pseudohalogen" as used herein is a molecule consisting of two or more electronegative atoms that is similar to a halogen in a free state and can produce an anion similar to a halide ion. Examples of pseudohalogens are cyanide, cyanate, thiocyanate, azide, or a combination thereof.
[0100] The halogen atom may be, for example, iodine (I), chlorine (Cl), bromine (Br), fluorine (F), or a combination thereof, and the pseudohalogen may be, for example, cyanide, cyanate, thiocyanate, azide, or a combination thereof.
[0101] The trivalent anion may be, for example, N 3- .
[0102] According to another embodiment, the garnet-based solid electrolyte may be an oxide represented by Formula 3
[0103] Formula 3
[0104] Li 3+x La 3 Zr 2-a M a O 12
[0105] Wherein M in Formula 3 may be Al, Ga, In, Si, Ge, Sn, Sb, Bi, Sc, Y, Ti, Hf, V, Nb, Ta, W, or a combination thereof, and x may be a number from 1 to 10, and 0≤a<2.
[0106] An example of a garnet-based solid electrolyte is Li 7 La 3 Zr 2 O 12 and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 .
[0107] The garnet-based solid electrolyte may have a -1The garnet-based solid electrolyte can be prepared in various thicknesses over a wide temperature range.
[0108] The sulfide solid electrolyte is not particularly limited as long as it includes sulfur (S) or a sulfur-based element (Se, Te) and has suitable ionic conductivity. For example, the sulfide solid electrolyte may include one or more of the following: Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiX (where X is a halogen element), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn, or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , and Li 2 S-SiS 2 -Li p MO q(where p and q are positive numbers, and M can be one of P, Si, Ge, B, Al, Ga, and In). When the sulfide solid electrolyte material includes Li 2 S-P 2 S 5 When it is, the mixed molar ratio of Li 2 S and P 2 S 5 can be selected in the range of 50:50 to 90:10, can be selected in the range of 60:40 to 90:10, or can be selected in the range of 75:25 to 90:10. The sulfide solid electrolyte can be prepared as follows: treating starting materials (such as Li 2 S, P 2 S 5 etc.) by a melt quenching method, a mechanical grinding method, etc. In addition, calcination can be carried out after the treatment.
[0109] The sulfide solid electrolyte may include a compound represented by Formula 4.
[0110] Formula 4
[0111] Li a M1 x PS y M2 z M3 w
[0112] Regarding Formula 4, M1 can be one or more metal elements other than Li selected from Groups 1 to 15 of the periodic table, and M2 can be one or more elements selected from Group 17 of the periodic table, and
[0113] M3 can be SO n , and can satisfy the following conditions: 4 ≤ a ≤ 8, 0 ≤ x < 1, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 ≤ w < 2, and 1.5 ≤ n ≤ 5.
[0114] Regarding Formula 4, z can be 0 < z ≤ 5, 0 < z ≤ 4, 0 < z ≤ 3, 0 < z ≤ 2, 0.2 ≤ z ≤ 1.8, 0.5 ≤ z ≤ 1.8, 1.0 ≤ z ≤ 1.8, or 1.0 ≤ z ≤ 1.5.
[0115] Regarding Formula 4, 5 ≤ a ≤ 8, 0 ≤ x ≤ 0.7, 4 ≤ y ≤ 7, 0 < z ≤ 2, and 0 ≤ w ≤ 0.5, for example, 5 ≤ a ≤ 7, 0 ≤ x ≤ 0.5, 4 ≤ y ≤ 6, 0 < z ≤ 2, and 0 ≤ w ≤ 0.2, for example, 5.5 ≤ a ≤ 7, 0 ≤ x ≤ 0.3, 4.5 ≤ y ≤ 6, 0.2 ≤ z ≤ 1.8, and 0 ≤ w ≤ 0.1, for example, 5.5 ≤ a ≤ 6, 0 ≤ x ≤ 0.05, 4.5 ≤ y ≤ 5, 1.0 ≤ z ≤ 1.5, and 0 ≤ w ≤ 0.1.
[0116] Regarding the compound represented by Formula 4, for example, M1 may include Na, K, Mg, Ag, Cu, Hf, In, Ti, Pb, Sb, Fe, Zr, Zn, Cr, B, Sn, Ge, Si, Zr, Ta, Nb, V, Ga, Al, As, or a combination thereof. M1 may be, for example, a monovalent cation or a divalent cation.
[0117] Regarding the compound represented by Formula 4, for example, M2 may include F, Cl, Br, I, or a combination thereof. M2 may be, for example, a monovalent anion.
[0118] Regarding the compound represented by Formula 4, for example, SO of M3 n Can be S 4 O 6 , S 3 O 6 , S 2 O 3 , S 2 O 4 , S 2 O 5 , S 2 O 6 , S 2 O 7 , S 2 O 8 、SO 4 、SO 5 , or a combination thereof. n It may be, for example, a divalent anion. SO n 2- It can be, for example, S 4 O 6 2- , S 3 O 6 2- , S 2 O 3 2- , S 2 O 4 2- , S 2 O 5 2- , S 2 O 6 2- , S 2 O 7 2- , S 2 O 8 2- 、SO 4 2- 、SO 5 2- , or a combination thereof.
[0119] For example, the compound represented by Formula 4 may be a compound selected from the compounds represented by Formulas 4a to 4b below.
[0120] Formula 4a
[0121] Li a PS y M2 z M3 w
[0122] Regarding Formula 4a, M2 is one or more elements from Group 17 of the periodic table, M3 is SO n , and 4 ≤ a ≤ 8, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 < w < 2, and 1.5 ≤ n ≤ 5.
[0123] Formula 4b
[0124] Li a M1 x PS y M2 z M3 w
[0125] Regarding Formula 4b, M1 is one or more metal elements other than Li from Groups 1 to 15 of the periodic table, and M2 is one or more elements from Group 17 of the periodic table,
[0126] M3 is SO n , 4 ≤ a ≤ 8, 0 < x < 1, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 < w < 2, and 1.5 ≤ n ≤ 5.
[0127] Regarding Formulas 4a and 4b, 0 < z ≤ 5, 0 < z ≤ 4, 0 < z ≤ 3, 0 < z ≤ 2, 0.2 ≤ z ≤ 1.8, 0.5 ≤ z ≤ 1.8, 1.0 ≤ z ≤ 1.8, or 1.0 ≤ z ≤ 1.5. Regarding Formulas 4a and 4b, for example, 5 ≤ a ≤ 8, 4 ≤ y ≤ 7, 0 < z ≤ 2, and 0 ≤ w ≤ 0.5; 5.5 ≤ a ≤ 7, 4.5 ≤ y ≤ 6, 0.2 ≤ z ≤ 1.8, and 0 ≤ w ≤ 0.1; 0.5 ≤ z ≤ 1.8; or 1.0 ≤ z ≤ 1.8.
[0128] For example, the compound represented by Formula 4 may be the compound represented by Formula 5 below.
[0129] Formula 5
[0130] Li 7-m×v-z M4 v PS 6-z M5 z1 M6 z2
[0131] Among them, M4 is Na, K, Mg, Ag, Cu, Hf, In, Ti, Pb, Sb, Fe, Zr, Zn, Cr, B, Sn, Ge, Si, Zr, Ta, Nb, V, Ga, Al, As, or a combination thereof, m is the oxidation number of M4, M5 and M6 are each independently F, Cl, Br, or I, and 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 < 1, 0 < z < 2, z = z1 + z2, and 1 ≤ m ≤ 2.
[0132] For example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2. For example, 0 < v ≤ 0.5, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2. For example, 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2. For example, 0 < v ≤ 0.1, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.5 ≤ z ≤ 1.8, and z = z1 + z2. For example, 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2. M4 can be, for example, one type of metal element or two types of metal elements.
[0133] For example, the compound represented by Formula 5 may include one type of halogen element or two types of halogen elements.
[0134] For example, the compound represented by Formula 5 may be a solid ion conductor compound represented by Formulas 5a to 5f.
[0135] Formula 5a
[0136] Li 7-z PS 6-z M5 z1 M6 z2
[0137] Formula 5b
[0138] Li 7-v-z Na v PS 6-z M5 z1 M6 z2
[0139] Formula 5c
[0140] Li 7-v-z K v PS 6-z M5 z1 M6 z2
[0141] Formula 5d
[0142] Li7-v-z Cu v PS 6-z M5 z1 M6 z2
[0143] Formula 5e
[0144] Li 7-2v-z Mg v PS 6-z M5 z1 M6 z2
[0145] Formula 5f
[0146] Li 7-v-z Ag v PS 6-z M5 z1 M6 z2
[0147] In these formulas, M5 and M6 can each independently be F, Cl, Br, or I,
[0148] 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 < 1, 0 < z < 2, and z = z1 + z2.
[0149] Regarding Formulas 5a to 5f, the following conditions can each independently be satisfied: for example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.5, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2; 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2, for example, 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.5, and z = z1 + z2. The v in Formula 5a is 0.
[0150] The compound represented by Formula 4 can be, for example, a compound represented by one of the following formulas:
[0151] Li 7-z PS 6-z F z1 , Li 7-z PS 6-z Cl z1 , Li 7-z PS 6-z Br z1 , Li 7-z PS 6-z I z1 , Li 7-zP.S. 6-z F z1 Cl z2 ,Li 7- z P.S. 6-z F z1 Br z2 ,Li 7-z P.S. 6-z F z1 I z2 ,Li 7-z P.S. 6-z Cl z1 Br z2 ,Li 7-z P.S. 6-z Cl z1 I z2 ,Li 7-z P.S. 6-z Cl z1 F z2 ,Li 7- z P.S. 6-z Br z1 I z2 ,Li 7-z P.S. 6-z Br z1 F z2 ,Li 7-z P.S. 6-z Br z1 Cl z2 ,Li 7-z P.S. 6-z I z1 F z2 ,Li 7-z P.S. 6-z I z1 Cl z2 ,Li 7- z P.S. 6-z I z1 Br z2 ,Li 7-v-z Na v P.S. 6-z F z1 ,Li 7-v-z Na v P.S. 6-z Cl z1 ,Li 7-v-z Na v P.S. 6-z Br z1 ,Li 7-v-z Na v P.S. 6-z I z1 ,Li 7-v-zNa v P.S. 6-z F z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z F z1 Br z2 ,Li 7-v-z Na v P.S. 6-z F z1 I z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 Br z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 I z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 F z2 ,Li 7-v-z Na v P.S. 6-z Br z1 I z2 ,Li 7-v-z Na v P.S. 6-z Br z1 F z2 ,Li 7-v-z Na v P.S. 6-z Br z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z I z1 F z2 ,Li 7-v-z Na v P.S. 6-z I z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z I z1 Br z2 ,Li 7-v-z K v P.S. 6-z F z1 ,Li 7-v-z K v P.S. 6-z Cl z1,Li 7-v-z K v P.S. 6-z Br z1 ,Li 7-v-z K v P.S. 6-z I z1 ,
[0152] Li 7-v-z K v P.S. 6-z F z1 Cl z2 ,Li 7-v-z K v P.S. 6-z F z1 Br z2 ,Li 7-v-z K v P.S. 6-z F z1 I z2 ,Li 7-v-z K v P.S. 6- z Cl z1 Br z2 ,Li 7-v-z K v P.S. 6-z Cl z1 I z2 ,Li 7-v-z K v P.S. 6-z Cl z1 F z2 ,Li 7-v-z K v P.S. 6-z Br z1 I z2 ,Li 7-v-z K v P.S. 6- z Br z1 F z2 ,Li 7-v-z K v P.S. 6-z Br z1 Cl z2 ,Li 7-v-z K v P.S. 6-z I z1 F z2 ,Li 7-v-z K v P.S. 6-z I z1 Cl z2 ,Li 7-v-zK v PS 6- z and z1 Br z2 ,
[0153] them 7-v-z With v PS 6-z F z1 ,Li 7-v-z With v PS 6-z Cl z1 ,Li 7-v-z With v PS 6-z Br z1 ,Li 7-v-z With v PS 6-z and z1 ,Li 7-v- z With v PS 6-z F z1 Cl z2 ,Li 7-v-z With v PS 6-z F z1 Br z2 ,Li 7-v-z With v PS 6-z F z1 and z2 ,Li 7-v-z With v PS 6-z Cl z1 Br z2 ,Li 7-v- z With v PS 6-z Cl z1 and z2 ,Li 7-v-z With v PS 6-z Cl z1 F z2 ,Li 7-v-z With v PS 6-z Br z1 and z2 ,Li 7-v-z With v PS 6-z Br z1 F z2 ,Li 7-v- z Withv PS 6-z Br z1 Cl z2 ,Li 7-v-z Cu v PS 6-z I z1 F z2 ,Li 7-v-z Cu v PS 6-z I z1 Cl z2 ,Li 7-v-z Cu v PS 6-z I z1 Br z2 ,
[0154] Li 7-2v-z Mg v PS 6-z F z1 ,Li 7-2v-z Mg v PS 6-z Cl z1 ,Li 7-2v-z Mg v PS 6-z Br z1 ,Li 7-2v-z Mg v PS 6-z I z1 ,
[0155] Li 7-2v-z Mg v PS 6-z F z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z F z1 Br z2 ,Li 7-2v-z Mg v PS 6-z F z1 I z2 ,Li 7-2v- z Mg v PS 6-z Cl z1 Br z2 ,Li 7-2v-z Mg v PS 6-z Cl z1 I z2 ,Li 7-2v-z Mg v PS6-z Cl z1 F z2 ,Li 7-2v-z Mg v PS 6-z Br z1 I z2 ,Li 7-2v-z Mg v PS 6-z Br z1 F z2 ,Li 7-2v-z Mg v PS 6-z Br z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z I z1 F z2 ,Li 7-2v-z Mg v PS 6-z I z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z I z1 Br z2 ,
[0156] Li 7-v-z Ag v PS 6-z F z1 ,Li 7-v-z Ag v PS 6-z Cl z1 ,Li 7-v-z Ag v PS 6-z Br z1 ,Li 7-v-z Ag v PS 6-z I z1 ,Li 7-v- z Ag v PS 6-z F z1 Cl z2 ,Li 7-v-z Ag v PS 6-z F z1 Br z2 ,Li 7-v-z Ag v PS 6-z F z1 I z2 ,Li7-v-z Ag v PS 6-z Cl z1 Br z2 , Li 7-v- z Ag v PS 6-z Cl z1 I z2 , Li 7-v-z Ag v PS 6-z Cl z1 F z2 , Li 7-v-z Ag v PS 6-z Br z1 I z2 , Li 7-v-z Ag v PS 6-z Br z1 F z2 , Li 7-v- z Ag v PS 6-z Br z1 Cl z2 , Li 7-v-z Ag v PS 6-z I z1 F z2 , Li 7-v-z Ag v PS 6-z I z1 Cl z2 , or Li 7-v-z Ag v PS 6-z I z1 Br z2 .
[0157] In the above formula, the following conditions can be satisfied independently of each other: 0 < v ≤ 0.7, 0 < z1 < 2, 0 < z2 < 1, 0 < z < 2, and z = z1 + z2; for example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 < z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2; 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2; or 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.2, 1.0 ≤ z ≤ 1.5, and z = z1 + z2. When v, z1, or z2 does not exist in the above formula, v = 0, z1 = 0, or z2 = 0. For example, when z1 = 0, z = z2. For example, when z2 = 0, z = z1.
[0158] The compound represented by Formula 4 may belong to, for example, the cubic crystal system and, more particularly, to the F-43m space group. Additionally, as described above, the compound represented by Formula 4 may be a thiogermanate sulfide having a thiogermanate crystal structure. The compound represented by Formula 4 includes, for example, one or more of a monovalent cation element and a divalent cation element that replace a part of the lithium sites in the thiogermanate crystal structure, or includes a foreign halogen element, or includes a substituted SO n anion, and thus, the lithium ion conductivity can be further improved, and the electrochemical stability against lithium metal can be further improved.
[0159] The compound represented by Formula 4 may be, for example, Li 6 PS 5 Cl.
[0160] The sulfide solid electrolyte used herein may be a thiogermanate compound including one or more selected from the following: Li 7-x PS 6-x Cl x , 0 ≤ x ≤ 2; Li 7-x PS 6-x Br x , 0 ≤ x ≤ 2; and Li 7-x PS 6-x I x , where x satisfies the condition 0 ≤ x ≤ 2. In particular, the sulfide solid electrolyte included in the solid electrolyte may be a thiogermanate compound including one or more selected from the following: Li 6 PS 5 Cl, Li 6 PS 5 Br, and Li 6 PS 5 I.
[0161] The sulfide solid electrolyte may be in a powder or molded form. The molded solid electrolyte may be in the form of, for example, a pellet, a sheet, or a film, but is not necessarily limited thereto and may have various forms depending on the application.
[0162] The example of polymer solid electrolyte is polyethylene oxide, polypropylene oxide, polystyrene (PS), polyphosphazene, polysiloxane, polyvinylidene fluoride-to-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), or its combination. The ionic conductivity of the polymer solid electrolyte can be achieved by the local segment motion of the polymer. The polymer solid electrolyte can be prepared by mixing a polyether with a plasticizer salt and sometimes some liquid plasticizers. The electrolyte can be prepared into a film using a solvent evaporation coating method. However, it is not limited thereto, and any suitable polymer solid electrolyte available in the art can be used.
[0163] If desired, the solid electrolyte may further include a binder. The binder included in the solid electrolyte layer 1 may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these. The binder may be any suitable material that can be used as a binder in the relevant technical field.
[0164] An all-solid-state battery according to further example embodiments may include: a positive electrode including a positive electrode current collector and a positive electrode active material layer; and the subassembly described above.
[0165] The positive electrode includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may use a metal substrate. Examples of the metal substrate are aluminum (Al), indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector may be in a plate shape or a foil shape. The positive electrode current collector may be omitted.
[0166] The positive electrode active material of the positive electrode active material layer may be used without limitation as long as it is generally used in lithium batteries. For example, the positive electrode active material may be a composite oxide of one or more types of lithium and a metal selected from cobalt, manganese, nickel, and a combination thereof, and a specific example thereof may be a compound represented by one of the following formulae: Li a A 1-b B' b D' 2 (where 0.90 ≤ a≤ 1.8, and 0 ≤ b ≤ 0.5); Li a E 1-b B' b O 2-c D' c(where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, and 0 ≤ c ≤ 0.05); LiE 2-b B' b O 4-c D' c (where 0 ≤ b ≤ 0.5, and 0 ≤ c ≤ 0.05); Li a Ni 1-b- c Co b B' c D' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α ≤ 2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 <α < 2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤0.05, and 0 < α < 2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c≤ 0.05, and 0 < α ≤ 2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α < 2); Li a Ni 1-b-c Mn b B' c O 2-α F' 2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α < 2); Li aNi b E c G d O 2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, and 0.001 ≤ d ≤ 0.1.); Li a Ni b Co c Mn d G e O 2 (where 0.90 ≤ a ≤1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤0.5, and 0.001 ≤ e ≤ 0.1.); Li a NeG b O 2 (where 0.90 ≤ a ≤ 1.8, and 0.001 ≤ b ≤ 0.1.); Li a CoG b O 2 (where 0.90 ≤ a ≤ 1.8, and 0.001 ≤ b ≤ 0.1.); Li a MnG b O 2 (where 0.90 ≤ a ≤ 1.8, and 0.001 ≤ b ≤ 0.1.); Li a Mn 2 G b O 4 (where 0.90 ≤ a ≤ 1.8, and 0.001 ≤ b ≤ 0.1.); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 2 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (0 ≤ f ≤ 2); Li (3-f) Fe 2 (PO 4 ) 3 (0 ≤ f ≤ 2); and LiFePO 4. With respect to these formulas, A may be Ni, Co, Mn, or a combination thereof; B' may be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D' may be O, F, S, P, or a combination thereof; E may be Co, Mn, or a combination thereof; F' may be F, S, P, or a combination thereof; G may be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q may be Ti, Mo, Mn, or a combination thereof; I' may be Cr, V, Fe, Sc, Y, or a combination thereof; and J may be V, Cr, Mn, Co, Ni, Cu, or a combination thereof. For example, the positive electrode active material may include one or more types selected from the following: lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, iron oxide, and vanadium oxide. For example, the positive electrode active material may be LiCoO 2 、LiMn x O 2x (x=1, 2), LiNi 1-x Mn x O 2 (0 <x<1)、LiNi 1-x-y Co x Mn y O 2 (0≤x≤0.5, 0≤y≤0.5), LiFePO 4 、TiS 2 , FeS 2 、TiS 3 , FeS 3 wait.
[0167] The positive electrode active material layer may further include an ionic liquid electrolyte. The ionic liquid electrolyte may be non-volatile. An ionic liquid refers to a salt in a liquid state at room temperature or a room temperature molten salt having a melting point below room temperature and is composed only of ions. The ionic liquid may be one selected from the following compounds: a) one or more cations selected from the following: ammonium-based cations, pyrrolidine-based cations, Cations based on pyridine Cationic, pyrimidine-based Cation, imidazole-based Cation, based on piperidine Cationic, pyrazole-based Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, cations based on triazole cations, and mixtures thereof; and b) one or more anions selected from the following: BF 4 - PF 6 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - 、(FSO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - , and (CF 3 SO 2 ) 2 N - For example, the ionic liquid may include one or more selected from the following: bis(trifluoromethanesulfonyl)imide N-methyl-N-propylpyrrolidine , bis(trifluoromethanesulfonyl)imide N-butyl-N-methylpyrrolidine , bis(trifluoromethanesulfonyl)imide 1-butyl-3-methylimidazole , and bis(trifluoromethanesulfonyl)imide 1-ethyl-3-methylimidazole The polymeric ionic liquid may include repeating units comprising: a) one or more cations selected from the group consisting of ammonium-based cations, pyrrolidine-based cations, Cations based on pyridine Cationic, pyrimidine-based Cation, imidazole-based Cation, based on piperidine Cationic, pyrazole-based Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, cations based on triazole cations, and mixtures thereof; and b) one or more anions selected from the following: BF 4 - PF 6 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - ,(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - 、NO 3 - 、Al 2 Cl 7 - ,(CF 3 SO 2 )3 C - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , SF 5 CF 2 SO 3 - , SF 5 CHF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , and (O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - .
[0168] The ionic liquid electrolyte may be filled inside the pores of the surface of the positive electrode active material layer in contact with the solid electrolyte layer. The content of the ionic liquid electrolyte may be from about 0.1 parts by weight to about 20 parts by weight, from about 0.1 parts by weight to about 15 parts by weight, from about 0.1 parts by weight to about 10 parts by weight, or from about 0.1 parts by weight to about 5 parts by weight, based on 100 parts by weight of the positive electrode active material layer not including the ionic liquid electrolyte. Including an ionic liquid electrolyte may result in an increased ionic conductivity, which improves the charge and discharge characteristics of the battery.
[0169] The positive electrode active material layer may further include a conductive material and a binder. For example, the conductive material may include carbon black, carbon fiber, graphite, or a combination thereof. For example, the carbon black may be acetylene black, Ketjen black, Super P carbon black, channel black, furnace black, lamp black, pyrolytic carbon black, or a combination thereof. Graphite may be natural graphite or artificial graphite. A combination of at least two of the foregoing materials may be used. In addition to the conductive materials described above, the positive electrode active material layer may additionally include conductive materials of different compositions. Additional conductive materials include: conductive fibers such as metal fibers; fluorocarbon powders; metal powders such as aluminum powders or nickel powders; conductive whiskers such as zinc oxide or potassium titanate; polyethylene derivatives; or a combination thereof. The content of the conductive material may be in the range of about 1 part by weight to about 10 parts by weight, such as about 2 parts by weight to about 7 parts by weight, based on 100 parts by weight of the positive electrode active material. When the amount of the conductive material is within these ranges, such as about 1 part by weight to about 10 parts by weight, the conductivity of the positive electrode may be sufficient.
[0170] The binder can improve the adhesion between the components of the positive electrode and to the positive electrode current collector. Examples of the binder are polyacrylic acid (PAA), polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluorinated rubber, copolymers thereof, or combinations thereof. The content of the binder may be in the range of about 1 part by weight to about 10 parts by weight, for example, about 2 parts by weight to about 7 parts by weight, based on 100 parts by weight of the positive electrode active material. When the binder content is within these ranges, the adhesion of the positive electrode active material layer to the positive electrode current collector may be further improved, and the reduction in the energy density of the positive electrode active material layer may be suppressed.
[0171] Solvents such as N-methylpyrrolidone, acetone, and water may be used. The contents of the positive electrode active material, conductive material, binder, and solvent are at levels generally used in lithium batteries.
[0172] A plasticizer may be added to the positive active material composition to form pores inside the positive active material layer.
[0173] The all-solid-state battery may include a thin film stacked battery, a stacked ceramic battery, a lithium-sulfur battery, or a lithium-air battery. For example, the all-solid-state battery may be an all-solid secondary battery.
[0174] According to another example embodiment, a method for preparing an all-solid-state battery includes: preparing a solid electrolyte molded body; providing a solid electrolyte layer having an uneven surface by surface-treating the solid electrolyte molded body; preparing a solid electrolyte layer having one surface on which an intermediate layer containing a porous carbon material is formed by applying and drying a composition containing a porous carbon material; obtaining a first stack including the negative electrode current collector / the intermediate layer containing a porous carbon material / the solid electrolyte layer / a first metal lithium / a first metal foil by: disposing the negative electrode current collector on the intermediate layer containing a porous carbon material, and attaching the first metal foil having the first metal lithium disposed thereon to the solid electrolyte layer and the intermediate layer containing the porous carbon material formed thereon; on another surface opposite to the surface of the intermediate layer of the material; obtaining a second stack comprising the negative electrode current collector / a second intermediate layer containing a porous carbon material having pores without lithium / a first intermediate layer containing a porous carbon material having pores partially or completely filled with lithium by pre-lithiation of the first stack under vacuum / the solid electrolyte layer / the first metallic lithium / the first metal foil; forming a third intermediate layer containing a metal by: removing the first metal foil on which the first metallic lithium is disposed from the second stack, and disposing a second metal foil between the second intermediate layer containing a porous carbon material and the negative electrode current collector, thereby forming the subassembly described above; and disposing a positive electrode on the solid electrolyte layer of the subassembly.
[0175] Using the methods described above, an all-solid-state battery with a reinforced mechanical structure and improved charge / discharge characteristics can be fabricated.
[0176] Figure 3A A schematic process flow chart showing a method for preparing a negative electrode portion including a solid electrolyte layer and an intermediate layer according to an embodiment, and Figure 3B A schematic process flow chart showing a method for preparing an all-solid-state battery according to an embodiment.
[0177] like Figure 3A and 3B As shown in , a solid electrolyte molded body 11 is prepared. The solid electrolyte molded body 11 can be produced, for example, by heat-treating a precursor of a solid electrolyte material, particularly an oxide solid electrolyte material.
[0178] The oxide solid electrolyte may be prepared by contacting the precursors in stoichiometric amounts to form a mixture, and heat treating the mixture. Contact may include grinding, such as ball milling or crushing (grinding). The mixture of precursors mixed in a stoichiometric composition may be subjected to a first heat treatment in an oxidizing atmosphere to prepare a first heat-treated product. The first heat treatment may be performed at a temperature range of less than 1000°C for 1 hour to 36 hours. The product of the first heat treatment may be crushed. The crushing of the first heat-treated product may be performed dry or wet. Wet crushing may be performed, for example, by mixing the first heat-treated product with a solvent such as methanol and then grinding the mixture for 0.5 to 10 hours using a ball mill or the like. Dry crushing may be performed by grinding, such as ball milling, in the absence of a solvent. The particle diameter of the crushed first heat-treated product may be about 0.1 μm to about 10 μm, or about 0.1 μm to about 5 μm. The crushed first heat-treated product may be dried. The crushed first heat-treated product can be mixed with a binder solution and formed into a disc, or simply pressed at a pressure of about 1 ton to about 10 tons to form a disc. The molded body can be subjected to a second heat treatment at a temperature of less than or equal to 1000°C for 1 hour to 36 hours. The solid electrolyte molded body 11 as a sintered product is obtained by the second heat treatment. The second heat treatment can be carried out, for example, at 550°C to 1000°C. The first heat treatment time can be 1 hour to 36 hours. In order to obtain a sintered product, the second heat treatment temperature can be higher than the first heat treatment temperature. For example, the second heat treatment temperature can be 10°C or more, 20°C or more, 30°C or more, or 50°C or more than the first heat treatment temperature. The molded product can be subjected to a second heat treatment in one or more atmospheres of an oxidizing atmosphere and a reducing atmosphere. The second heat treatment can be carried out in a) an oxidizing atmosphere, b) a reducing atmosphere, or c) an oxidizing atmosphere and a reducing atmosphere. Alternatively, the oxide solid electrolyte can be prepared using a tape casting method. For example, an oxide solid electrolyte slurry is prepared by mixing an oxide solid electrolyte powder with a binder and a solvent. The oxide solid electrolyte slurry is ball milled for 12 to 24 hours and aged for 1 to 4 hours. The aged oxide solid electrolyte slurry is poured onto a scraper set at a predetermined height, and a strip casting is performed by moving the PET substrate film at a speed of about 1.0 m / min to about 3.0 m / min to obtain a raw sheet having a thickness of tens of microns. The raw sheet is subjected to a stacking process, a pressing process, and a cutting process and sintered at a temperature of 1000°C to 1350°C to obtain a sintered body. The sintered body can be set in a mold and pressurized to prepare a solid electrolyte molded body 11 having a thickness of several hundred microns.
[0179] Next, the solid electrolyte molded body 11 is surface treated to provide a solid electrolyte layer 11' having an uneven treated surface. As described above, the surface treatment includes chemical treatment, electrolytic polishing, and, for example, acid treatment and drying may be performed to obtain a solid electrolyte layer 11' having an uneven treated surface. The acid treatment may be performed using hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, hydrofluoric acid, or a mixture of these acids. For example, the acid treatment may be performed at a concentration of about 0.1 M to about 10 M for 30 minutes to 1 hour. For example, the acid treatment may be performed at a concentration of about 0.1 M to about 1 M for 30 minutes to 1 hour. After the acid treatment, washing with, for example, ethanol and then drying in a drying chamber may be performed to obtain a solid electrolyte layer 11' having an uneven surface.
[0180] Next, the porous carbon material-containing composition 12 is applied to one surface of the solid electrolyte layer 11'. Thereafter, the solid electrolyte layer 11' coated with the porous carbon material-containing composition is dried to produce the solid electrolyte layer 11' on which the porous carbon material-containing intermediate layer 12' is formed.
[0181] The composition 12 containing porous carbon material may include one-dimensional porous carbon material and three-dimensional porous carbon material. The composition 12 containing porous carbon material may further include two-dimensional porous carbon material. The composition 12 containing porous carbon material may further include metal nanoparticles, metal nanowires, metal nanotubes, metal nanofibers, metal nanosheets, metal nanorods, or alloys thereof. The composition 12 containing porous carbon material may further include a binder. The specific types and contents of the carbon material, metal material, and binder included in the composition 12 containing porous carbon material are the same as described above, and therefore the following description will be omitted. Non-limiting examples of application methods include scraper, rod coating, screen printing, spraying, etc. The thickness of the intermediate layer 12 'containing porous carbon material may be, for example, from about 0.1 μm to about 20 μm.
[0182] Next, the negative electrode current collector 16 is disposed on the intermediate layer 12' containing a porous carbon material, and the first metal foil 18 on which the first metal lithium 17 is disposed is attached to the other surface of the solid electrolyte layer 11' opposite to the surface on which the intermediate layer 12' containing a porous carbon material is formed, so as to obtain a first laminate including the negative electrode current collector 16 / intermediate layer 12' containing a porous carbon material / solid electrolyte layer 11' / first metal lithium 17 / first metal foil 18. The first metal foil 18 may include a material that does not react with lithium (i.e., does not form any alloy or compound with lithium). The first metal foil 18 may include the same material as the material for the negative electrode current collector 6 described above.
[0183] Next, the first stack is pre-lithiated under vacuum to obtain a second stack including a negative electrode current collector 16 / a second intermediate layer 13 containing a porous carbon material having pores without lithium / a first intermediate layer 12'' containing a porous carbon material having pores partially or completely filled with lithium / a solid electrolyte layer 11' / a first metal lithium 17 / a first metal foil 18. In order to create a vacuum environment, the first stack is arranged inside a bag and sealed. The pre-lithiation is carried out at a temperature between about 25°C and about 60°C. The pre-lithiation process is carried out as follows: the solid electrolyte layer 11' and the negative electrode current collector 16 on which the intermediate layer 12' containing a porous carbon material is formed are wrapped with a first metal foil 18 on which the first metal lithium 17 is arranged. Under the condition that direct electrical contact is achieved between the negative electrode current collector 16 and the metal lithium, electrons move from the negative electrode current collector 16 to the solid electrolyte layer 11' due to the potential difference between the metal lithium and the porous carbon material. Lithium ions are released from the first metal lithium 17 into the solid electrolyte layer 11'. The lithium ions in the solid electrolyte layer 11' are embedded in the porous carbon material to form a lithium (LiC 6 ) to obtain charge neutrality. Due to the pre-lithiation process, the all-solid-state battery is not easily short-circuited and its initial coulombic efficiency (ICE) does not deteriorate even when charging and discharging are repeatedly performed.
[0184] Next, the bag is removed, and the first metal foil 18 on which the first metal lithium 17 is provided is removed from the second laminate. Thereafter, the second metal foil is provided between the second intermediate layer 13 containing the porous carbon material and the negative electrode current collector 16 to produce a negative electrode-solid electrolyte layer subassembly in which the third intermediate layer 14 containing the metal is formed.
[0185] The positive electrode is arranged on the solid electrolyte layer 11' of the negative electrode-solid electrolyte layer subassembly, thereby completing the manufacture of the battery. The positive electrode active material layer 21 may include an ionic liquid electrolyte and a positive electrode active material as described above. The uneven surface of the solid electrolyte layer 11' in contact with the positive electrode active material layer 21 and the interior of the positive electrode may be impregnated with the ionic liquid electrolyte. The battery is prepared as follows: the pre-lithiated negative electrode-solid electrolyte layer subassembly and the positive electrode are arranged in an aluminum bag and sealed under vacuum. At this time, a portion of each of the positive electrode collector 22 and the negative electrode collector 16 is allowed to protrude from the aluminum bag so as not to break the vacuum of the battery, thereby forming a positive terminal and a negative terminal, respectively.
[0186] Hereinafter, embodiments and comparative examples of the present disclosure will be described. However, the following embodiments are merely examples of the present disclosure, and the present disclosure is not limited to the following embodiments.
[0187] Example
[0188] Example 1: Preparation of all-solid-state secondary battery
[0189] (Preparation of anode-solid electrolyte layer subassembly)
[0190] Prepare a Li with a thickness of 500 µm and a diameter of 14 mm. 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Solid electrolyte disc (Ta-doped LLZO, Toshima Co.). The LLZO solid electrolyte was acid-treated with 1 M hydrochloric acid for 30 minutes, then washed with ethanol and dried in a drying chamber to provide a Li-containing solid electrolyte disc having an uneven surface. 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The solid electrolyte layer of the solid electrolyte wafer.
[0191] Separately, carbon black (CB, ENSACO 250G, Imerys Co.) as a three-dimensional porous carbon material and single-walled carbon nanotube (SWCNT, TUBALL™ BATT H 2 O, 0.4%, OCSiAl) is added to a mixture including water and polyvinyl alcohol grafted polyacrylic acid (PVA-g-10PAA) as an aqueous binder, and then stirred using a mixer (Thinky Corporation, AR-100) to prepare a composition containing a porous carbon material. Polyvinyl alcohol grafted polyacrylic acid (PVA-g-10PAA) is synthesized by grafting acrylic acid monomers to a polyvinyl alcohol backbone according to the method described in J. He, L. Zhang, Journal of Alloys and Compounds 763 (2018) 228-240 (the contents of which are incorporated herein by reference in their entirety).
[0192] The composition containing the porous carbon material is applied to the Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The solid electrolyte layer of the solid electrolyte disc was dried at room temperature for 20 minutes to prepare a solid electrolyte layer having an intermediate layer containing a porous carbon material having a thickness of about 6.5 μm thereon. The intermediate layer containing the porous carbon material includes 94.8 wt % of carbon black, 0.2 wt % of single-walled carbon nanotubes, and 5 wt % of polyvinyl alcohol-grafted polyacrylic acid, based on the total weight of the intermediate layer.
[0193] A 10 μm thick copper negative electrode current collector was disposed on the intermediate layer containing the porous carbon material, and the other surface of the solid electrolyte layer with the surface on which the intermediate layer containing the porous carbon material was formed was wrapped with a 10 μm thick first copper foil (Honjo Metal Co., Ltd) on which a 20 μm thick first metal lithium was disposed to obtain a first laminate including a negative electrode current collector / intermediate layer containing a porous carbon material / solid electrolyte layer / first metal lithium / first copper foil.
[0194] The first stack is placed in a sealed aluminum bag and maintained at 60°C for 10 hours (pre-lithiation) to obtain a second stack comprising a negative electrode current collector / a second intermediate layer containing a porous carbon material having pores without lithium and having a thickness of about 2.5 µm / a first intermediate layer containing a porous carbon material having pores partially or completely filled with lithium and having a thickness of about 4 µm (pore size: 20 nm, porosity: 50%) / a solid electrolyte layer having a thickness of 500 µm / a first metal lithium having a thickness of 20 µm / a first copper foil having a thickness of 10 µm.
[0195] The second stack is taken out from the sealed aluminum bag, and the negative electrode collector and the first copper foil (Honjo Metal Co., Ltd) on which the first metallic lithium is disposed are removed therefrom, and then a 10 µm thick second lithium foil (Honjo Metal Co., Ltd) is disposed between the second intermediate layer containing porous carbon material and the negative electrode collector with a diameter of 13 mm to prepare the following negative electrode-solid electrolyte layer subassembly: wherein a copper-coated negative electrode collector having a thickness of 10 µm, a third intermediate layer containing lithium metal having a thickness of about 10 µm, a second intermediate layer containing porous carbon material having pores without lithium and having a thickness of about 2.5 µm, a first intermediate layer containing porous carbon material having pores partially or completely filled with lithium and having a thickness of about 4 µm, and a solid electrolyte layer having a thickness of 500 µm are arranged in the order of the statements.
[0196] (Preparation of positive electrode)
[0197] Preparation of LiCoO 2(LCO, Samsung SDI) as a positive electrode active material. Carbon black (Super P® Li, Imerys Co.) was prepared as a conductive material. Polyvinylidene fluoride (Solef® 5130, Solvay Co.) was prepared as a binder. The binder was used in the form of a solution dissolved in NMP at a ratio of 5% by weight. Then, these materials were mixed in a weight ratio of positive electrode active material: conductive material: binder = 94:3:3 to prepare a composition for forming a positive electrode active material layer. The composition was applied to a thickness of 46µm on a 9 µm thick aluminum foil (Nippon Foil Mfg. Co., LTD) current collector using an applicator, dried at 120°C for 12 hours, and then pressed to manufacture a positive electrode including a positive electrode active material layer.
[0198] The positive electrode active material layer of the prepared positive electrode is impregnated with an electrolyte 23 containing 1-ethyl-3-methylimidazole bis(fluorosulfonyl)imide dissolved in an ionic liquid. 2.0 M lithium bis(fluorosulfonyl)imide (LiFSI, 99.9%, water content < 10 ppm) in (EMIM-FSI, 99.9%, water content < 20 ppm, Kanto Chemical Co. Inc.).
[0199] (Preparation of all-solid-state secondary batteries)
[0200] The positive electrode was disposed on the negative electrode-solid electrolyte layer subassembly and sealed under vacuum to fabricate a 2032 type coin cell all-solid-state secondary battery.
[0201] Example 2: Preparation of all-solid-state secondary battery
[0202] A 2032-type coin-cell all-solid-state secondary battery was prepared in the same manner as in Example 1, except that when preparing a composition containing a porous carbon material, an intermediate layer containing the porous carbon material had a thickness of about 8 µm, carbon black (CB, C45, Imerys Co.) was used as a three-dimensional porous carbon material, and a second stack was obtained comprising: a negative electrode collector / a second intermediate layer containing a porous carbon material having pores that do not contain lithium and having a thickness of about 4 µm / a first intermediate layer containing a porous carbon material having pores that are partially or completely filled with lithium and having a thickness of about 4 µm (pore size: 20 nm, porosity: 50%) / a solid electrolyte layer having a thickness of 500 µm / a first metal lithium having a thickness of 20 µm / a first copper foil having a thickness of 10 µm.
[0203] Example 3: Preparation of all-solid-state secondary battery
[0204] A 2032-type coin cell all-solid-state secondary battery was prepared in the same manner as in Example 1, except that when preparing a composition containing a porous carbon material, silver nanoparticles having a diameter of 30 nm were added, and a solid electrolyte layer on which an intermediate layer containing a porous carbon material was formed was prepared, the intermediate layer containing a porous carbon material having a thickness of about 7.5 µm and comprising 60 wt % of carbon black, 0.2 wt % of single-walled carbon nanotubes, 34.8 wt % of silver nanoparticles, and 5 wt % of polyvinyl alcohol-grafted polyacrylic acid, based on the total weight of the intermediate layer, and a second laminate comprising: a negative electrode current collector / a second intermediate layer containing a porous carbon material having pores not containing lithium and having a thickness of about 3.5 µm / a first intermediate layer containing a porous carbon material having pores partially or completely filled with lithium and having a thickness of about 4 µm (pore size: 30 nm, porosity: 50%) / a solid electrolyte layer having a thickness of 500 µm / a first metal lithium having a thickness of 20 µm / a first metal lithium having a thickness of 10 The thickness of the first copper foil is µm.
[0205] Comparative Example 1: Preparation of all-solid-state secondary battery
[0206] A 2032-type coin-cell all-solid-state secondary battery was prepared in the same manner as in Example 1, except that when the composition containing the porous carbon material was prepared, a negative electrode-solid electrolyte layer subassembly was obtained according to the following method.
[0207] When preparing a composition containing a porous carbon material, a three-dimensional porous carbon material carbon black (CB, ENSACO250G, IMERYS Co.) is used alone as the porous carbon material, and a solid electrolyte layer is prepared on which an intermediate layer containing a porous carbon material is formed, wherein the intermediate layer containing the porous carbon material has a thickness of about 7 µm and includes 95 wt % of carbon black and 5 wt % of polyacrylic acid grafted with polyvinyl alcohol, based on the total weight of the intermediate layer.
[0208] A 10 µm thick copper negative electrode current collector was disposed on an intermediate layer containing a porous carbon material, and the other surface of the solid electrolyte layer on which the intermediate layer containing a porous carbon material was formed was wrapped with a 10 µm thick copper foil (Honjo Metal Co., Ltd) on which 20 µm thick lithium was disposed by cold isostatic pressing (CIP) at 25°C and 250 MPa for 3 minutes to form a subassembly including a negative electrode current collector / intermediate layer containing a porous carbon material / solid electrolyte layer / metal lithium / copper foil.
[0209] Comparative Example 2: Preparation of all-solid-state secondary battery
[0210] A 2032-type coin-cell all-solid-state secondary battery was prepared in the same manner as in Example 1, except that when preparing a composition containing a porous carbon material, a three-dimensional porous carbon material carbon black (CB, ENSACO250G, Imerys Co.) was used alone as the porous carbon material, a solid electrolyte layer on which an intermediate layer containing a porous carbon material was formed was prepared, the intermediate layer containing the porous carbon material having a thickness of about 7 µm and comprising 95 wt % of carbon black and 5 wt % of polyvinyl alcohol-grafted polyacrylic acid, based on the total weight of the intermediate layer, and a second stack comprising the following was obtained: a negative electrode collector / a second intermediate layer containing a porous carbon material having pores that do not contain lithium and having a thickness of about 20 nm / a first intermediate layer containing a porous carbon material having pores that are partially or completely filled with lithium and having a thickness of about 4 µm (pore size: 20 nm, porosity: 40%) / a solid electrolyte layer having a thickness of 500 µm / a first metal lithium having a thickness of 20 µm / a first copper foil having a thickness of 10 µm.
[0211] Comparative Example 3: Preparation of all-solid-state secondary battery
[0212] A 2032-type coin-cell all-solid-state secondary battery was prepared in the same manner as in Example 1, except that when preparing a composition containing a porous carbon material, a three-dimensional porous carbon material carbon black (CB, C45, Imerys Co.) was used alone as the porous carbon material, a solid electrolyte layer on which an intermediate layer containing a porous carbon material was formed was prepared, the intermediate layer containing the porous carbon material having a thickness of about 7 µm and comprising 95 wt % of carbon black and 5 wt % of polyvinyl alcohol-grafted polyacrylic acid, based on the total weight of the intermediate layer, and a second stack comprising the following was obtained: a negative electrode collector / a second intermediate layer containing a porous carbon material having pores that do not contain lithium and having a thickness of about 30 nm / a first intermediate layer containing a porous carbon material having pores that are partially or completely filled with lithium and having a thickness of about 4 µm (pore size: 30 nm, porosity: 40%) / a solid electrolyte layer having a thickness of 500 µm / a first metal lithium having a thickness of 20 µm / a copper foil having a thickness of 10 µm.
[0213] Evaluation Example 1: SEM-AES Analysis
[0214] The all-solid secondary battery prepared according to Example 1 was disassembled, and the negative electrode-solid electrolyte layer subassembly was analyzed by scanning electron microscopy (SEM) / Auger electron spectroscopy (AES). The SEM analysis results (cross-sectional view) are shown in Figure 4 and the AES analysis results (top view) are shown in Figure 5A , 5B , 5C, and 5D.
[0215] refer to Figure 4 , it can be seen that, with respect to the negative electrode-solid electrolyte layer subassembly of Example 1, in the case of the first intermediate layer containing porous carbon material in contact with the solid electrolyte layer, the layer containing porous carbon material having pores partially or completely filled with lithium is formed to a thickness of about 2.5 µm, and in the case of the second intermediate layer containing porous carbon material on the first intermediate layer containing porous carbon material, the layer containing porous carbon material having pores without lithium is formed to a thickness of about 4 µm.
[0216] refer to Figures 5A to 5D , confirming that after pre-lithiation in the negative electrode-solid electrolyte layer subassembly of Example 1, the first intermediate layer containing the porous carbon material includes lithium, carbon, and oxygen.
[0217] Evaluation Example 2: X-ray Photoelectron Spectroscopy (XPS) Analysis
[0218] The first stack of the all-solid secondary battery prepared according to Example 1 was packaged under vacuum and kept at 60° C. for 16 hours (pre-lithiation). Then, regarding the intermediate layer containing the porous carbon material on the solid electrolyte layer, the XPS analysis was performed. Figure 6 The surface of the intermediate layer from P1 (center) to P5 (edge) is shown in FIG. Fig. 7A , 7B , 7C, 7D, and 7E.
[0219] A Thermo Kα XPS equipped with monochromatic Al-Kα (hν = 1486.6 eV) was used as the XPS analysis instrument. The survey scan had a pass energy of 280 eV (1 eV / step) and each scan took 7 minutes. The HR core level scan had a pass energy of 55 eV (0.1 eV / energy step). For Ar + Ion sputtering, 1 kV accelerating voltage, 1 x 1 mm 2 The area was subjected to three cycles of 1 min each, followed by an accelerating voltage of 1 kV for 1 × 1 mm 2 The area was cycled for 2 min, and then the 1 x 1 mm area was accelerated at 2 kV. 2 The area was subjected to three cycles of 10 minutes each.
[0220] refer to Figures 7A to 7E It can be seen that the pre-lithiated intermediate layer containing porous carbon material of the all-solid-state secondary battery prepared according to Example 1 has a similar distribution of lithium, carbon, oxygen, and chlorine from P1 (center) to P5 (edge).
[0221] Therefore, it can be seen that in the all-solid secondary battery prepared according to Example 1, the possibility of local current concentration is reduced because lithium is uniformly deposited due to pre-lithiation, resulting in a reduction in the risk of short circuit during charge and discharge.
[0222] Evaluation Example 3: Charge / Discharge Experiment (I)
[0223] The all-solid-state secondary batteries according to Example 1, Example 2, and Comparative Examples 1 to 3 were placed in a constant temperature bath at 25°C.
[0224] For each all-solid-state secondary battery, the first cycle was performed at 0.3 mA / cm 2 The battery was charged at a constant current of 0.3 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0225] The second to fourth cycles were performed at 0.5 mA / cm 2 The battery was charged at a constant current of 0.5 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0226] The 5th to 7th cycles were performed at 1.0 mA / cm 2 The battery was charged at a constant current of 1.0 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0227] The 8th to 10th cycles were performed at 1.6 mA / cm 2 The battery was charged at a constant current of 1.6 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0228] The 11th to 13th cycles were performed at 2.0 mA / cm 2 The battery was charged at a constant current of 2.0 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0229] The 14th to 16th cycles were performed at 2.5 mA / cm 2 The battery was charged at a constant current of 2.5 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.75 V.
[0230] After the 17th cycle, the battery was charged at 1.6 mA / cm 2 The battery was charged at a constant current of 1.6 mA / cm 2 Discharge was repeatedly performed at a constant current of 2.5 Å until the battery voltage reached 2.75 V, and the area capacity (AC) was examined. A total of 26 charge and discharge cycles were performed.
[0231] In all charge / discharge cycles, there was a 1 minute pause after one charge / discharge cycle. The results are shown in Fig. 8A , 8B , 8C, 8D, and 8E.
[0232] refer to Fig. 8A The all-solid-state secondary battery prepared according to Example 1 showed a value of about 2.85 mAh / cm for a total of 26 cycles. 2 Up to 3.4 mAh / cm 2 The stable capacity per area. Figure 8B The all-solid-state secondary battery prepared according to Example 2 showed a low areal capacity of about 2.75 mAh / cm during the other cycles for a 10th cycle charge cutoff voltage of 4.1 V. 2 Up to 3.35 mAh / cm 2 The stable capacity per area. Figure 8C and 8D The all-solid-state secondary batteries prepared according to Comparative Examples 1 and 2 had a capacity of about 2.6 mAh / cm for a total of 26 cycles. 2 Up to 3.3 mAh / cm 2 and about 2.75 mAh / cm 2 Up to 3.35 mAh / cm 2 It was found that the capacity per area was wide compared to Example 1. Fig. 8E The all-solid-state secondary battery prepared according to Comparative Example 3 showed 2.05 mAh / cm for a total of 26 cycles. 2 Up to 3.3 mAh / cm 2 Very wide range of capacities per area.
[0233] Evaluation Example 4: Charging / discharging experiment (II)
[0234] The all-solid-state secondary batteries prepared according to Example 1, Example 2, and Comparative Examples 1 to 3 were charged and discharged in a constant temperature bath at 25°C in the same manner as in Evaluation Example 3, but the charging and discharging test was performed for a total of 30 cycles. The results are shown in Fig. 9A and 9B middle.
[0235] refer to Fig. 9A and 9B The all-solid-state secondary batteries prepared according to Example 1, Example 2, Comparative Example 1, and Comparative Example 2, excluding the all-solid-state secondary battery prepared according to Comparative Example 3, showed stable charge / discharge characteristics without short circuit. Among these, the all-solid-state secondary battery prepared according to Example 1 had the highest capacity per area and the highest capacity retention rate up to 30 cycles.
[0236] Among these, at 0.09 C rate (0.3 mA / cm 2 ) and 0.5 C rate (1.6 mA / cm 2 ) The capacity per area at the current density is shown in Table 1.
[0237] Table 1
[0238]
[0239] Referring to Table 1, compared with the all-solid-state secondary batteries prepared according to Comparative Examples 1 to 3, the all-solid-state secondary batteries prepared according to Examples 1 and 2 have a higher rate of 0.09 C (0.3 mA / cm 2 ) and 0.5 C rate (1.6 mA / cm 2 ) has a higher capacity per area at a current density of .
[0240] A subassembly for use in an all-solid-state battery according to one aspect is configured so that a negative electrode current collector, an intermediate layer, and a solid electrolyte layer are arranged in the order stated, wherein in its initial state or fully discharged state, the intermediate layer includes: a first intermediate layer containing a porous carbon material, which has pores partially or completely filled with lithium and is in contact with the solid electrolyte layer; a second intermediate layer containing a porous carbon material, which has pores without lithium and is located on the first intermediate layer containing the porous carbon material; and a third intermediate layer containing a metal on the second intermediate layer containing the porous carbon material and in contact with the negative electrode current collector. The intermediate layer can provide fast lithium transport (supply / removal), resulting in improved charge / discharge characteristics, and can strengthen the mechanical structure to improve unit cell performance.
[0241] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. The description of features or aspects in each embodiment should typically be considered to be applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes in form and detail may be made therein without departing from the spirit and scope as defined by the appended claims.
Claims
1. Subcomponents, including: Anode current collector; Middle layer; and A solid electrolyte layer, wherein the intermediate layer is between the negative electrode current collector and the solid electrolyte layer, wherein in an initial state or a fully discharged state, the intermediate layer comprises a first intermediate layer containing a porous carbon material, which contacts the solid electrolyte layer and includes a porous carbon material having pores partially or completely filled with lithium, a second intermediate layer containing a porous carbon material, which includes pores not containing lithium and is disposed on the first intermediate layer containing a porous carbon material, and A third intermediate layer containing metal is in contact with the negative electrode current collector and is on the second intermediate layer containing the porous carbon material, wherein the third intermediate layer containing metal includes metal.
2. The subassembly of claim 1, wherein The first intermediate layer containing the porous carbon material has a pore size of 10 nanometers to 1 micrometer and a porosity of 30% to 60%.
3. The subassembly of claim 1, wherein The first intermediate layer containing a porous carbon material and the second intermediate layer containing a porous carbon material each include a one-dimensional porous carbon material and a three-dimensional porous carbon material.
4. The subassembly of claim 3, wherein The one-dimensional porous carbon material comprises carbon nanotubes, carbon nanofibers, carbon nanowires, carbon nanorods, carbon nanoribbons, carbon nanobelts, or a combination thereof, and The three-dimensional porous carbon material includes carbon black particles, graphite particles, carbon nanoflowers, carbon nanoprisms, carbon nanodiamonds, or a combination thereof.
5. The subassembly of claim 3, wherein The one-dimensional porous carbon material is an electrical conductor, and The three-dimensional porous carbon material is a lithium conductor.
6. The subassembly of claim 3, wherein The first intermediate layer containing a porous carbon material and the second intermediate layer containing a porous carbon material each further include a two-dimensional porous carbon material.
7. The subassembly of claim 6, wherein The two-dimensional porous carbon material includes graphene, carbon nanosheets, carbon plates, carbon flakes, MXene, or a combination thereof.
8. The subassembly of claim 1, wherein The first intermediate layer containing a porous carbon material and the second intermediate layer containing a porous carbon material each further include metal nanoparticles, metal nanowires, metal nanotubes, metal nanofibers, metal nanosheets, metal nanorods, alloys thereof, or combinations thereof.
9. The subassembly of claim 1, wherein The first intermediate layer containing a porous carbon material and the second intermediate layer containing a porous carbon material each include a binder, and The content of the binder is 0.1 wt % to 7 wt % based on the total weight of the first intermediate layer containing the porous carbon material and the second intermediate layer containing the porous carbon material.
10. The subassembly of claim 1, wherein A thickness ratio of the thickness of the second intermediate layer containing the porous carbon material to the thickness of the first intermediate layer containing the porous carbon material is 1:0.5 to 1:
5.
11. The subassembly of claim 1, wherein The first intermediate layer containing the porous carbon material has a thickness of 1 μm to 5 μm.
12. The subassembly of claim 1, wherein The first intermediate layer containing the porous carbon material is a pre-lithiation layer.
13. The subassembly of claim 1, wherein The third intermediate layer containing metal includes lithium, indium, gallium, alloys thereof, or combinations thereof.
14. The subassembly of claim 1, wherein The surface of the solid electrolyte layer in contact with the first intermediate layer containing the porous carbon material is a treated surface.
15. The subassembly of claim 1, wherein The solid electrolyte layer includes an oxide solid electrolyte, a sulfide solid electrolyte, a polymer solid electrolyte, or a combination thereof.
16. All-solid-state batteries, including: A positive electrode comprising a positive electrode current collector and a positive electrode active material layer on the current collector; and A subassembly according to any one of claims 1 to 15 on the positive electrode.
17. A method for preparing an all-solid-state battery, the method comprising: preparing a solid electrolyte shaped body; performing a surface treatment on the solid electrolyte shaped body to provide a treated surface; applying an intermediate layer containing a porous carbon material on one side of the solid electrolyte layer, drying the intermediate layer containing the porous carbon material to prepare the solid electrolyte layer having the intermediate layer containing the porous carbon material on one side; Disposing the negative electrode current collector on the intermediate layer containing the porous carbon material; attaching a first metal foil on which a first metal lithium is disposed to a surface of the solid electrolyte layer opposite to a surface on which the intermediate layer containing a porous carbon material is disposed, to obtain a first stack including the negative electrode current collector / the intermediate layer containing a porous carbon material / the solid electrolyte layer / the first metal lithium / the first metal foil; Pre-lithiating the first stack under vacuum to obtain a second stack including the negative electrode current collector / the second intermediate layer containing a porous carbon material having pores not containing lithium / the first intermediate layer containing a porous carbon material having pores partially or completely filled with lithium / the solid electrolyte layer / the first metal lithium / the first metal foil; removing the first metal foil on which the first metal lithium is disposed from the second stack; and disposing a second metal foil between the second intermediate layer containing the porous carbon material and the negative electrode current collector to form a third intermediate layer containing metal, thereby preparing the subassembly as claimed in any one of claims 1 to 15; and A positive electrode is disposed on the solid electrolyte layer of the subassembly to prepare the all-solid-state battery.
18. The method of claim 17, wherein The surface treatment includes chemical treatment, electrolytic polishing, wet polishing, argon plasma etching, oxygen plasma cleaning, annealing, or exposure to high vacuum.
19. The method of claim 17, wherein The pre-lithiation is carried out at a temperature of 25°C to 60°C.
20. The method of claim 17, wherein The intermediate layer containing the porous carbon material includes a one-dimensional porous carbon material and a three-dimensional porous carbon material.
Citation Information
Patent Citations
Processing device and method for manufacturing processed products
KR1020230124085A
Anchovy fish sauce residue seasoning material manufacturing method including acid decomposition step
KR1020240125245A